Enhancing EFL Students’ Environmental Awareness and Motivation through a Faith-Based Green ELT Curriculum - Scipio, Jane Elvira; Mangangue, Jeane; Tumuju, Vivi Nansy; Suot, Royke Max; Kalangi, Jola Silvana; Lumentah, Lenda; Lalira, James Edward (Universitas Hamzanwadi, 2025)
Integrating sustainable education into English as a Foreign Language (EFL) has become increasingly important in response to global environmental challenges. This study evaluates the effectiveness of a localised Green ELT curriculum developed and implemented at a private Christian university in Tomohon, Indonesia. Guided by a Design-Based Research (DBR) methodology, the curriculum was designed to integrate ecological content with Christian values and English language learning objectives. The study involved 50 purposively selected EFL students and was conducted over three months (March–May 2025) through three phases: curriculum design, classroom implementation, and evaluation. Data were collected using pre- and post-questionnaires, classroom observations, and Focus Group Discussions (FGDs). Quantitative data were analysed with paired t-tests, while qualitative data were thematically analysed. The findings revealed statistically significant improvements in both environmental awareness (t = -13.62, p < 0.001) and motivation to learn English (t = -6.60, p < 0.001). Qualitative insights further confirmed that faith-based discussions and contextualised activities deepened student engagement, linking language learning to sustainability issues. These results demonstrate that Green ELT can foster linguistic skills while enhancing students’ sense of environmental responsibility when localised and aligned with cultural and religious values. The study highlights the potential of Green ELT in faith-based contexts and recommends further adaptation across diverse educational settings to promote sustainable language education.